القواعد الفقهية المتعلقة بالمعاملات المالية عند إبن العربي من خلال كتابه المسالك وتطبيقاتها المعاصرة - جديد الجودي (University of M'Sila, 2025)
Praise be to God, Lord of the worlds, praise his blessings and reward his more, and prayers and peace be upon Muhammad Abdullah and his Messenger, may God bless him and his family and his companions, and whoever traces his impact. And after: This is the summary of the doctoral thesis tagged with: "The jurisprudential rules related to the financial transactions of Ibn Al -Arabi through his book of paths and their contemporary applications." Key words: jurisprudence rules, contemporary financial transactions, Abu Bakr Ibn Al -Arabi, paths. Where the study dealt with the jurisprudential rules broadcast in the book of the paths of Imam Ibn Al -Arabi, which are related to contemporary financial transactions, they formed from an introduction, and a chapter paving up in theoretical, three applied chapters, and a conclusion. The introductory separation touched on the theoretical side, and it contains a translation of Imam Abi Bakr Ibn Al -Arabi and the definition of his book in explaining the Munta of Imam Malik, then the definition of jurisprudence rules and what is related to them, from the emergence, development and ingredients, then introducing contemporary financial transactions, the assets upon which the jurisprudence of transactions in Islam, and the types of financial transactions. The three chapters were also exposed to the applied side: the major jurisprudential rules, contemporary applications, small jurisprudential rules related to passport and proof and their contemporary applications, small jurisprudential rules related to prevention, and their contemporary applications. Where each rule was displayed according to seven demands, which are mentioning the places of the rule in the paths, then introducing the vocabulary of the base, then mentioning the total meaning of the rule, and then rooting the rule, then mentioning the formulas Then conclusion: It has the most important results and recommendations.